Teachers' Perceptions of Physical literacy. Issue 4 (7th May 2021) - Stoddart, Alexandra L.; Humbert, M. Louise
Abstract: The purpose of this study was to explore what current physical education specialists and generalists know and understand about physical literacy and how the concept is operationalised in physical education. Six teachers from an urban school district in Canada participated in semi‐structured interviews as part of a larger physical literacy intervention study. Interviews were audio‐recorded and transcribed verbatim. Transcripts were thematically analysed. Three themes were generated from the data: (a) 'Never really used that word [physical literacy] before', (b) 'Well, we do have outcomes' and (c) 'What do you guys want to play'? Findings demonstrated that the majority of teachers in this study, regardless of being a specialist or generalist, exhibited limited understanding regarding the overall concept of physical literacy. This illuminates the need for all teachers to be better supported to understand and develop physical literacy through their physical education classes.